Hubungan Minat Membaca dengan Kemampuan Literasi Sains Peserta Didik pada Pembelajaran Biologi - Afifah, Annisa; Fuadiyah, Sa’diatul (MASALIQ, 2025)
This research is motivated by the limited systematic studies that discuss the relationship between reading interest and science literacy skills in the context of biology learning, despite the significant impact this phenomenon has on the achievement of students' 21st-century competencies. The purpose of this study is to identify, evaluate, and synthesize relevant research findings on the relationship between reading interest and students' science literacy. The method employed was a Systematic Literature Review (SLR) using a descriptive qualitative approach. This review analyzed 15 scientific articles published between 2013 and 2024, selected based on topic-specific inclusion criteria, methodological quality, and relevance to the context of biology education. Data were analyzed using thematic synthesis in accordance with the PRISMA protocol. The results indicated that reading interest has a positive and significant correlation with science literacy; however, this relationship is enhanced by mediating factors such as the quality of reading materials, literacy-based learning models, the role of teachers, and digital literacy. These findings support the scientific literacy approach in biology learning and contribute to the theoretical framework regarding the integration of affective and cognitive dimensions in science education. The primary conclusion of this study is that enhancing students' science literacy should involve increasing their interest in reading, selecting relevant teaching materials, and providing adaptive pedagogical and technological support. The implications of this study include the development of literate learning strategies in schools, the formulation of context-based literacy policies, and opportunities for further research on digital literacy and family involvement in strengthening the reading culture.